The Correlation Between Students’ English Achievement and Their Homework at the Eleventh Grade Students of SMA Negeri 3 Oku - Arizah, Mila; Sari, Santi Novita (ETERNAL (English Teaching Journal), 2019)
The aim of this research was to observe on the correlation between students? English achievement and their homework at the eleventh grade students of SMA Negeri 3 OKU. The kind of research that  was used is quantitative and the design is correlational. The Writer used questionnaire and students? achievement in English subject to collect the data. The questionnaire measured the effect of homework on students. The population of this research was the eleventh grade students of SMA Negeri 3 OKU in academic year 2018/2019. Sample was taken by using Slovin formula. Population was 272 students. Sample was 162 students. The students? mean score of questionnaire was 13.62. The students? mean score of students? English achievement was 77.21 and it was in good category. Based on the result of the data, writers found that there was significant correlation between students? English achievement and their homework. The correlation was significant in terms of the correlation coefficient was 0.485. It meant English homework can influenced students? English achievement.